2012
DOI: 10.1016/j.neuroimage.2011.11.079
|View full text |Cite
|
Sign up to set email alerts
|

From novel to familiar: Tuning the brain for metaphors

Abstract: Metaphors are fundamental to creative thought and expression. Newly coined metaphors regularly infiltrate our collective vocabulary and gradually become familiar, but how does this shift from novel to conventionalized meaning happen in the brain? We investigated the neural career of metaphors in a functional magnetic resonance imaging study using extensively normed new metaphors and simulated the ordinary, gradual experience of metaphor conventionalization by manipulating participants’ exposure to these metaph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
122
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(137 citation statements)
references
References 54 publications
8
122
2
Order By: Relevance
“…Rather, motor cortex engagement appears to be modulated by familiarity: Highly conventional figurative uses of verbs, as are found in idioms, do not engage M1/SMA (Aziz-Zadeh, Wilson, Rizzolatti, & Iacoboni, 2006;Raposo, Moss, Stamatakis, & Tyler, 2009), but less familiar metaphoric senses may (Desai et al, 2011;Obert et al, 2014). Similarly, Cardillo et al (2012) observed that pMTG activation was graded by familiarity with action verb metaphors. These studies provide preliminary support for previous hypotheses that the degree of sensorimotor engagement is determined by metaphor novelty, such that sensorimotor areas are more strongly recruited for understanding novel figurative senses of words than for conventional ones (Aziz-Zadeh & Damasio, 2008;Cardillo et al, 2010).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Rather, motor cortex engagement appears to be modulated by familiarity: Highly conventional figurative uses of verbs, as are found in idioms, do not engage M1/SMA (Aziz-Zadeh, Wilson, Rizzolatti, & Iacoboni, 2006;Raposo, Moss, Stamatakis, & Tyler, 2009), but less familiar metaphoric senses may (Desai et al, 2011;Obert et al, 2014). Similarly, Cardillo et al (2012) observed that pMTG activation was graded by familiarity with action verb metaphors. These studies provide preliminary support for previous hypotheses that the degree of sensorimotor engagement is determined by metaphor novelty, such that sensorimotor areas are more strongly recruited for understanding novel figurative senses of words than for conventional ones (Aziz-Zadeh & Damasio, 2008;Cardillo et al, 2010).…”
mentioning
confidence: 94%
“…In partial support of these hypotheses, the emerging picture seems to be that both hemispheres, and especially bilateral prefrontal cortex, are recruited when deriving a new figurative sense. In a novel familiarization task, Cardillo et al (2012) parametrically varied participant experience with novel nominal and predicate metaphors to test for a right-left shift in lateralization with increased familiarity. Instead, their results indicated that the more familiar a metaphor was, the less it engaged a subset of the same regions necessary for comprehending the metaphor for the first time [inferior frontal gyrus (IFG) bilaterally, left posterior middle temporal gyrus (pMTG), and right postero-lateral occipital cortex].…”
mentioning
confidence: 99%
“…Similarly, Broca's region activation has also been found to go down as participants adapt to novel metaphors (Cardillo, Watson, Schmidt, Kranjec, & Chatterjee, 2012).…”
Section: Broca's Area and Within-sentence Contextual Effectsmentioning
confidence: 93%
“…Contrary to this is the finding by Raposo et al (2009), who measured the activation of motor and premotor cortices with three action verb conditions. Isolated action verbs (kick) and sentences with literal use of action verbs (kick the ball) activated the premotor cortex, while sentences with idiomatic use of action verbs (kick the bucket) did not (see also Aziz-Zadeh et al (2006) novelty (Cardillo et al, 2012; and context (Schuil et al, 2013). Cardillo et al (2012) directed attention to novelty as a factor through investigating the shift from novel to conventionalized metaphors and how the brain is tuned to this process.…”
Section: Introductionmentioning
confidence: 99%
“…Isolated action verbs (kick) and sentences with literal use of action verbs (kick the ball) activated the premotor cortex, while sentences with idiomatic use of action verbs (kick the bucket) did not (see also Aziz-Zadeh et al (2006) novelty (Cardillo et al, 2012; and context (Schuil et al, 2013). Cardillo et al (2012) directed attention to novelty as a factor through investigating the shift from novel to conventionalized metaphors and how the brain is tuned to this process. Schuil et al (2013) showed that sentential context modulates the degree to which motor regions are activated.…”
Section: Introductionmentioning
confidence: 99%